2015
DOI: 10.1111/1440-1681.12424
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of patterns of spontaneous adverse drug reaction reporting with St. John's Wort and fluoxetine during the period 2000–2013

Abstract: Herbal medicines are perceived to be safe by the general public and medical practitioners, despite abundant evidence from clinical trials and case reports that show herbal preparations can have significant adverse effects. The overall impact of adverse events to herbal medicines in Australia is currently unknown. Post marketing surveillance of medications through spontaneous adverse drug reaction (ADR) reports to the Therapeutic Goods Administration (TGA) is one way to estimate this risk. The patterns of spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 25 publications
0
13
1
1
Order By: Relevance
“…Moreover, in the absence of allergy workup these reports may be misleading. On the other hand, the patterns of ADRs seen here is markedly different to other herbal medicines reported through the TGA system 14 15. In particular, Echinacea, a known allergen, had fewer reports associated with hypersensitivity (53%) and all were mild 15…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Moreover, in the absence of allergy workup these reports may be misleading. On the other hand, the patterns of ADRs seen here is markedly different to other herbal medicines reported through the TGA system 14 15. In particular, Echinacea, a known allergen, had fewer reports associated with hypersensitivity (53%) and all were mild 15…”
Section: Discussioncontrasting
confidence: 82%
“…These patients are also more likely to be using other medication(s) for the same or another medical condition. This is an important consideration when contemplating glucosamine and chondroitin administration, given that published data shows that ADRs to complementary medicines are most severe when taken concomitantly with conventional medicines 14 15. Regardless, this drug combination is often recommended as an adjunct to traditional prescription pharmaceuticals and non-pharmacological treatments 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a review of popular herbal preparations found SJW interacted with more medications than any of the other herbs and dietary supplements [54]. Post-marketing surveillance of spontaneous adverse drug reactions indicated that SJW produced a similar adverse event profile to fluoxetine, with mild and severe adverse events more common with SJW while life-threatening events were more common with fluoxetine but still occurred [55]. While reports of rare adverse events cannot be dismissed based on RCT data, it is noteworthy that SJW appears to have fewer adverse events than antidepressant medication in the reported comparative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect is in particular relevant to patients with severe depression. Post-marketing surveillance in Australia found that, though SJW was not often given with an SSRI, there was a high proportion of adverse effects when this occurred, including a report of life-threatening serotonin syndrome [55]. While concerns about potential drug interactions will have prompted researchers to not provide patients with SJW in addition to standard antidepressant medication, we also did not identify studies that evaluated the effect of SJW treatment adjunctive to psychotherapy.…”
Section: Discussionmentioning
confidence: 99%